Management techniques applied to the construction industry - Oxley, R.; Poskitt, Joe ([Place of publication not identifed] : Blackwell Publishers, 1996)
Now in its 5th edition, this well established text first examines individual management techniques and then demonstrates these in practice, via a large new section of case studies based on actual building projects. This edition also features a revised section on costing and a new set of exercises for students.
General introduction and quality assurance; Management Techniques -- Planning generally; Bar charts; Project network techniques; Programming for repetitive construction generally; Sequence studies; Line of balance technique; Work study; Budgetary and cost control; Case Studies; Exercises
Includes bibliographical references and index.
Keywords: CONSTRUCTION INDUSTRY -- MANAGEMENT